In or out? Poverty dynamics among older individuals in the UK - Ricky Kanabar (University of Essex, Institute for Social and Economic Research (ISER), 2016)
Using the largest household panel survey Understanding Society, this paper investigates low income dynamics among pensioner households in the UK controlling for biases due to initial conditions and non-random survey attrition. Estimation results indicate the presence of a correlation between initial and conditional poverty status, specifically, there is regression toward the mean. The results find no evidence of a correlation between initial poverty status, conditional poverty status and survey attrition. The findings show the importance of benefit income in determining poverty status, suggesting that a dichotomous measure such as poverty status may not suitably reflect actual pensioner living standards. Aside from benefit income, receipt of employer and occupational pension, health, education and subjective financial situation are important in determining initial and conditional poverty status. Stylised examples highlight the significant differences in the "poverty experience" which arise due to differences individual and household characteristics.
Keywords: D31; J26; 330; old age poverty; retirement; understanding society